1993
DOI: 10.1111/j.1751-1097.1993.tb09551.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Proteoglycans in Ultraviolet‐irradiated Skin

Abstract: The effect of UVB exposure on the distribution and synthesis of dermal proteoglycans was measured in the skin of hairless mice. Two groups of mice were included: one was irradiated for 10 weeks; the other was kept as control. After intraperitoneal injection of sodium 35-S-sulfate, punch biopsies were taken for histology and proteoglycans were extracted from the remaining skin with 4 M guanidinium chloride, containing 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate (0.5%, weight per volume). Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 50 publications
2
10
0
1
Order By: Relevance
“…In agreement with onr findings on tbe effect of UVR alone, Margelin et al [33] found increased glycosaminoglycan synthesis in explants from UV-inadiated hairless mice. However, the increase was seen only in the proteoglycans beparin and heparan sulfate.…”
Section: Discussionsupporting
confidence: 52%
“…In agreement with onr findings on tbe effect of UVR alone, Margelin et al [33] found increased glycosaminoglycan synthesis in explants from UV-inadiated hairless mice. However, the increase was seen only in the proteoglycans beparin and heparan sulfate.…”
Section: Discussionsupporting
confidence: 52%
“…Chronically UVB-irradiated hairless mouse skin was observed to contain and produce increased HS and heparin proteoglycans (18). In contrast, Iriyama et al (17) reported that HS staining in the dermal-epidermal junction was decreased in acute UVB-irradiated buttock skin, while perlecan core protein and total HS staining did not change, probably through induction of heparanase activity by UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, staining for decorin is faint in young rats and distinct in old rats [35]. There are several reports concerning the changes in proteoglycan levels in photoaging, especially UVB irradiation [36,37]. UVB radiation markedly increases proteoglycan synthesis in mice [36].…”
Section: Effects Of Tobacco Smoke In Vivomentioning
confidence: 98%
“…There are several reports concerning the changes in proteoglycan levels in photoaging, especially UVB irradiation [36,37]. UVB radiation markedly increases proteoglycan synthesis in mice [36]. Versican and decorin immunostaining is increased in photoaged tissue samples accompanied by similar alterations in gene expression [37].…”
Section: Effects Of Tobacco Smoke In Vivomentioning
confidence: 99%